2021
DOI: 10.7150/jca.49676
|View full text |Cite
|
Sign up to set email alerts
|

Differences Related to Cancer Screening by Minority and Rural/Urban Status in the Deep South: Population-based Survey Results

Abstract: Objective: Cancer mortality in the U.S. Deep South exceeds national levels. A cross-sectional survey was undertaken across Alabama to discern cancer beliefs and screening practices, and compare data from racial/ethnic minority versus majority and rural versus urban respondents. Methods: Using population-based methods, we approached 5,633 Alabamians (ages 50-80) to complete a 58-item survey (administered in-person, via telephone, or the web). Descriptive statistics were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
(24 reference statements)
1
9
0
Order By: Relevance
“…The results of the present review were therefore controversial; namely, a rural-urban difference in colorectal cancer mortality was not obviously proven. Of note, the present findings appear to be in line with the results reported by Daniel et al 1 . While Daniel et al hypothesized that rural residents often acknowledge a family history of cancer and cope with it well, more studies are warranted to clarify the detailed reasons for these findings.…”
supporting
confidence: 94%
See 2 more Smart Citations
“…The results of the present review were therefore controversial; namely, a rural-urban difference in colorectal cancer mortality was not obviously proven. Of note, the present findings appear to be in line with the results reported by Daniel et al 1 . While Daniel et al hypothesized that rural residents often acknowledge a family history of cancer and cope with it well, more studies are warranted to clarify the detailed reasons for these findings.…”
supporting
confidence: 94%
“…We read with great interest the recent study by Daniel et al, which showed a different response to knowledge and practice in relation to colorectal cancer screening between minority and majority populations in the deep south of the U.S. 1 . As Daniel et al stated 1 , rurality is a possible contributor to increased mortality in patients with colorectal cancer because several factors related to lifestyle, and socioeconomics and healthcare systems are associated with the diagnosis and clinical course of this disease. Thus, the study assumed the difference in responses to colorectal cancer screening between rural and urban residents - interestingly, however, few differences were found 1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An exception occurred for residents of rural Clay County where an intensive face-to-face cancer prevention and control effort was underway; there, paper surveys were administered randomly to individuals in the community (e.g., dollar store, senior center, health department); paper-based surveys also were administered in the more urban Mobile County area to achieve balance in survey mode between rural: urban counties and adequate representation across counties. Given that the survey also collected data on cancer screening (data reported in another article), [9] solicitations were directed toward county residents who were 50-80 years of age. Individuals not opting-out or not completing the survey within two weeks were telephoned up to six times.…”
Section: Methodsmentioning
confidence: 99%
“…Diversifying the field of radiology is a major goal of many radiology departments and professional organizations, but comparable studies on how radiologist demographics may influence patients' perceptions of their radiology care are lacking [9]. This is especially important for breast imaging, which is challenged by screening mammography adherence and racial/ethnic disparities in breast cancer outcomes [10][11][12]. As patients may self-refer for screening mammography, and examinations are performed in the outpatient setting, there may be a gap in time between screening mammography and the next primary care provider contact.…”
Section: Introductionmentioning
confidence: 99%